Revision 2: an immunohistochemical approach and evaluation of solid pseudopapillary tumour of the pancreas. - Serra, S; Chetty, R (2008)
Solid pseudopapillary tumours (SPT) of the pancreas are uncommon, but with widespread and increased imaging, several of these lesions are coming to light incidentally and are subject to needle biopsies. On limited material and especially the solid or clear cell, variants of SPT can morphologically mimic most notably pancreatic neuroendocrine tumours and even metastatic renal cell carcinoma or melanoma. In this context, immunohistochemistry is important and useful in helping to reach the correct diagnosis. Several antibodies have been used in the immunohistochemical evaluation of SPT. As with most tumours, no one marker is specific, but rather a core panel is advocated. Recently, both beta-catenin and E-cadherin have been shown to be of value in SPT. Nuclear and cytoplasmic decoration of tumour cells by beta-catenin is seen in almost 100% of cases. This protein relocalisation away from the cell membrane is underscored by mutations of the beta-catenin gene. Mutations of the CDH1 gene are very uncommon in SPT, but the immunohistochemically detected changes to the protein are consistent and present in 100% of cases. Using an E-cadherin antibody to the extracellular domain of the molecule results in complete membrane loss, while the antibody directed to the cytoplasmic fragment produces distinct nuclear staining of the tumour cells. In addition, there is concordance of staining abnormalities between the two antibodies. When combined with CD10 and progesterone receptor positivity, a diagnosis of SPT can be rendered with confidence even in small biopsy samples.